PENGEMBANGAN MEDIA PUZZLE ANGKA UNTUK PENGENALAN LAMBANG BILANGANANAK USIA 4–5 TAHUN (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop valid, practical, and effective number puzzle media to improve the symbolic thinking skills of children aged 4–5 years. The research method uses the Rowntree development model which includes planning, development, and evaluation stages, and is complemented by Tessmer's formative evaluation which includes expert review, one-to-one evaluation, and small group evaluation. The research subjects consisted of 12 children, namely 3 children in the one-to-one evaluation stage and 9 children in the small group evaluation stage, while the object of the research was the number puzzle media. The instruments used included material expert validation sheets, media expert validation sheets, observation sheets, and teacher response questionnaires. The validation results showed that the number puzzle media was very valid with a score of 100% from material experts and 95% from media experts, with an overall average of 97%. The results of the practicality test showed that the media was very practical to use, with a score of 93% in the one-to-one evaluation stage and 96% in the small group evaluation stage, thus obtaining an average of 94%. This demonstrates that number puzzles are practical and effective, and can stimulate children's symbolic thinking skills, particularly in recognizing number shapes and relating them to the number of objects. Therefore, number puzzles are considered suitable for use as a learning tool for early childhood.